Political connections and depositor discipline - Mustafa Disli; Koen Schoors; Jos Meir (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
We examine the effects of political connections on depositor discipline in a sample of Turkish banks. Banks with former members of parliament at the helm enjoy reduced depositor discipline, especially if the former politician's party is currently in power - less so if the former politician served as a minister. Banks with structural problems are more likely to appoint former politicians, but our results remain robust after controlling for selection effects. Ministers may reduce depositor discipline less because they signal severe problems and because the additional government deposits they bring to the bank during their term tend to leave with them.
URN:NBN:fi:bof-201408072148
Keywords: G1; G2; D7; 330; Depositor discipline; political connections; banks